Meta analysis: The impact of utilizing rumen undegradable protein in feed on reproductive and production performance of dairy cow - Satyastika, Filza Zhafira; Samsudewa, Daud; Hartanto, Rudy (Journal of Advanced Veterinary Research, 2025)
The purpose of this research was to assess the reproductive and productive parameters of dairy cows with different levels of RUP. This study employed a methodology that involved scientific journal articles focusing on S/C, calving interval, conception rate, PPE, milk yield, milk protein, milk fat, milk lactose, and DMI. The findings indicated no significant differences in milk yield, composition, and reproductive metrics between cows administered RUP and those that were not (p>0.05). According to the NRC (2001), RUP levels constitute 6-10% of the total protein requirement for dairy cows. This study recommends that future research should ensure dairy cows receiving RUP are given the optimal dosage suited to their needs for more precise dosing.